The Impact of Vertical Fiscal Asymmetries on the Strength of Environmental Regulations - Shuai, Zhengtao (Transactions on Economics, Business and Management Research, 2024)
Deepening the financial system reform is an important part of economic high-quality development, and environmental regulation is a necessary path. Based on this, in the context of China's economic development increasingly pursuing the green transformation of the new era, this paper stands on the perspective of vertical fiscal asymmetry to explore the changes in the strength of environmental regulation. Based on the panel data of 30 provinces between 2007 and 2021, I empirically analyze the impact of vertical fiscal asymmetry on the strength of environmental regulation and how it works. It is shown that vertical fiscal asymmetry has an inhibitory effect on the strength of environmental regulation, and the results of the mode of action show that the increase in the degree of marketization weakens the inhibitory effect of vertical fiscal asymmetry on the strength of environmental regulation to a certain extent. Therefore, it is necessary to take measures such as continuing to deepen the reform of the fiscal system, deepening the reform of the industrial structure, and moderately expanding the degree of local marketization, in order to reduce the negative impact of vertical fiscal asymmetry on the strength of environmental regulation, and to contribute to ecological civilization.